Innovation forge: a hybrid review about resilience and technology readiness in the manufacturing sector - Nair, Kiran; Bhardwaj, Seema; Balasubramanian, Sreejith; Misra, Mahima; Chopra, Ritika (International journal of sustainable engineering, 2024)
This study addresses the gap in the comprehensive literature on the intersection of readiness technology and changes in the manufacturing sector. This study employs a hybrid review (bibliometric analysis and conceptual framework) to offer a panoramic overview of the field. We scrutinised 77 publications from peer-reviewed journals, from 2005 to 2023, using methodological lenses such as keyword co-occurrence networks and thematic maps. The review reveals the major contributors (publication trends, themes, and topics) to integrating 3D printing, additive manufacturing, Tech Competition and Lifecycle Assessment in Manufacturing, and Smart Manufacturing Strategies. Based on these insights, we advocate a focused research agenda to expand scholarly contributions to this field. We introduce a framework that offers a theoretically robust tool for scholars and practitioners studying the impact of technology readiness in the manufacturing sector. Consequently, this study not only distils the existing literature, but also sets the stage for future research. This study places significant emphasis on the implementation of technological solutions as a means to improve production operations. Additionally, this research emphasises the significance of ensuring that investment strategies follow the organisation's technological preparedness. An additional crucial implication concerns the cybersecurity protocols. This is consistent with the research's emphasis on investigating cybersecurity concerns in the manufacturing industry.